Overcoming causes of claim disputes in construction projects: a dematel based model - Siti Nur Farhain, Mohd Yusri (2023)
Claim disputes are inevitable as construction projects are renowned for being extremely complicated and loaded with risk and necessitate long-term collaboration among a variety of parties. Previous studies have only investigated the causes and effects of claim disputes in the construction sector; little have investigated the relationship between the different factors of causes and less on proposing strategies to overcome claim disputes. The aim of this study is to analyse the main causes of claim disputes in construction projects, and to propose strategies to avoid claim disputes in construction projects by adopting mixed method research that combines qualitative and quantitative data which utilizes DEMATEL method of data analysis by exploring the relationships between those factors. A list of causes and strategies for the study was produced from a review of the relevant literatures, with sixteen (16) causes and nine (9) strategies were retrieved. The approach known as Decision-Making Trial and Evaluation Laboratory, or DEMATEL, was applied to construct a causal relationship between the factors of causes and strategies with the goal of better comprehending these dynamics and finding effective ways to address them. According to the data obtained from thirteen (13) respondents, the primary contributing causes of claim disputes in construction projects are project cost underestimation (C7), poor communication among the parties (C15), contract violation (C4), contract misinterpretation (C5), contractor's financial difficulties (C3), variation order due to client's new requirements (C8), conflicting drawings and specifications (C14), and omissions and errors in design (C13). On the other hand, five (5) most significant strategies to overcome claim disputes in construction projects are RFI Procedure (S6), clarity of contract language (S2), effective communication (S3), Critical Path Method (CPM) (S8), and joint recognition of changes (S5). The findings of this study can provide significant assistance in developing a plan to effectively handle the issue of claim disputes that exists within the industry for the stakeholders in the construction sector and also, the government.